1998
DOI: 10.1161/01.cir.98.23.2608
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Atrial Denervation Creates Substrate for Sustained Atrial Fibrillation

Abstract: Background-Heterogeneous electrophysiological properties, which may be due in part to autonomic innervation, are important in the maintenance of atrial fibrillation (AF). We hypothesized that heterogeneous sympathetic denervation with phenol would create a milieu for sustained AF. Methods and Results-After the determination of baseline inducibility, 15 dogs underwent atrial epicardial phenol application and 11 underwent a sham procedure. After 2 weeks of recovery, the animals had repeat attempts at inducing AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 57 publications
4
63
1
Order By: Relevance
“…Experimental studies also suggested that ERP dispersion is an important factor in determining the ability to sustain AF [24,25]. Our results showed that dispersion of refractoriness is a suitable indicator of atrial vulnerability for the induction of AF.…”
Section: Atrial Refractory Periodssupporting
confidence: 61%
“…Experimental studies also suggested that ERP dispersion is an important factor in determining the ability to sustain AF [24,25]. Our results showed that dispersion of refractoriness is a suitable indicator of atrial vulnerability for the induction of AF.…”
Section: Atrial Refractory Periodssupporting
confidence: 61%
“…21,22 However, in recent studies we found that heterogeneous sympathetic denervation of the atria with the epicardial application of phenol in dogs resulted in increased heterogeneity of atrial refractoriness and a milieu for sustained AF. 12 In the present study, we found that heterogeneity of sympathetic innervation increases with prolonged rapid rates. We also found that this sympathetic heterogeneity is spatially related to heterogeneity of atrial refractoriness (as reflected by AFCL).…”
Section: Role Of Sympathetic Innervation In Electrical Remodeling and Afsupporting
confidence: 58%
“…The feasibility and methods of using [C-11]-labeled hydroxyephedrine (HED) to label atrial sympathetic nerve terminals have been previously described by our group. 12,14 HED was injected intravenously and arterial blood samples were drawn over a 30-minute period to calculate the available blood pool of HED. Two minutes before euthanasia, [F-18]-labeled microspheres of hydroxyapatite (20-to 40-m diameter) were injected into the left ventricular cavity and a continuous blood sample was drawn from the femoral artery at a predetermined rate to determine total atrial blood flow by the reference sample technique.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the characteristics of such remodeling is an increased heterogeneity in atrial refractoriness. Analogous to studies in ventricular arrhythmias, it has been proposed that a potential mechanism of such spatial dispersion of refractoriness could be the heterogeneity of autonomic innervation 99 . Thus, heterogeneous atrial denervation with application of phenol facilitated sustained AF in one study.…”
Section: Neuroreceptorial Remodelingmentioning
confidence: 99%